Role of glutamine metabolism in tuberculosis pathogenesis: a mini review - Parveen, Sadiya; Bishai, William R. (Frontiers in Tuberculosis, 2024)
Mycobacterium tuberculosis (Mtb) has remained one of the major infectious disease killers for generations and generations. In 2023 alone, this ancient disease was responsible for the death of 1.4 million individuals and has infected 10.6 million people. With the ever-evolving multi-and extremely resistant Mtb strains, the need for novel and effective drugs requiring shorter treatment regimens represents an urgent medical need for the development of new drugs. Over the last two decades, the field of host-directed therapy as a potential novel avenue for new approaches to TB treatment, either as a mono or adjuvant therapy, has garnered increasing attention. Among many host-directed targets, host immunometabolism has emerged as one of the most attractive targets for developing new host-directed therapies. As one of the most successful bacterial pathogens, Mtb has evolved several mechanisms to modulate numerous host metabolic pathways, including glycolysis, glutaminolysis, Kreb cycle, and oxidative phosphorylation. This mini review will focus on glutamine metabolism and its emergence as a potential target for treating tuberculosis (TB). In the last several decades, the role of glutamine metabolism in cancer and neurological disorders has been extensively studied. However, the association of glutamine metabolism with infectious disease has remained underappreciated. The aim of this review is to not only discuss the current knowledge in the field but also the existing knowledge gap that needs further exploration.